Combining elements of the CO-OP Approach™ with education to promote healthy eating among older adults: A pilot study - Dawson, Deirdre R.; Bar, Yael; Ajwani, Fatim; Rotenberg, Shlomit; Atlas, Barbara; Ricupero, Maria; Greewood, Carol; Parrott, Matthew D. (Frontiers in Rehabilitation Sciences, 2022)
This paper describes an exploratory study developing the Baycrest Brain-healthy Eating Approach (BBEA). Poor diet is a modifiable risk factor for many health problems including dementia. Mediterranean type diets, high in plant-based foods, rich in poly- and mono- unsaturated fatty acids with minimal consumption of saturated fat, red meat, and processed foods, are considered brain healthful. While several dementia prevention trials randomized controlled trials have included nutritional counselling in favor of these diets as one component of their interventions, the extent to which dietary change occurred is not known. Based on observations that a strategy training approach, the Cognitive Orientation to daily Occupational Performance (CO-OP) Approach, was beneficial for promoting lifestyle changes in older adults with complaints of cognitive changes, we undertook to develop the BBEA combining elements of CO-OP with didactic nutrition education. This exploratory, descriptive study assesses the feasibility and acceptability of the BBEA. Healthy community dwelling older adults (n=5) were recruited using convenience sampling. Participants received five, 2-hour, group sessions. During these sessions participants were supported in adopting dietary practices consistent with brain healthy eating. Each participant set specific dietary goals important to them. Feasibility of the intervention was demonstrated through high levels of attendance and by the findings that at each session, all participants set personally meaningful goals and received education on selected brain healthy eating topics. Acceptability was demonstrated through participants’ positive reports of their experiences and perspectives obtained via semi-structured interviews. Thus, the BBEA appears to be feasible and acceptable.